(untitled) (Hoboken, NJ, 2008)
A complete and comprehensive collaboration providing insight on future approaches to telephone survey methodology. Over the past fifteen years, advances in technology have transformed the field of survey methodology, from how interviews are conducted to the management and analysis of compiled data. Advances in Telephone Survey Methodology is an all—encompassing and authoritative resource that presents a theoretical, methodological, and statistical treatment of current practices while also establishing a discussion on how state—of—the—art developments in telecommunications have and will continue to revolutionize the telephone survey process.
Keywords: Surveys,Telephone surveys,Sự khảo sát,Điện thoại điều tra; Methodology,Technological innovations,Methodology,Technological innovations,Phương pháp,Đổi mới công nghệ,Phương pháp,Đổi mới công nghệ